Functional outcomes of the modified submandibular gland transfer procedure. (14th May 2019) - Murray, Scott; Chung, Jeffson; Zhang, Han; Baker, Sarah; Jha, Naresh; Scrimger, Rufus; Debenham, Brock; Biron, Vincent; Harris, Jeffery; O'Connell, Daniel; Seikaly, Hadi
Abstract : Objectives: Treatment for advanced head and neck cancers typically includes surgery followed by radiation therapy (RT). Radiation‐induced xerostomia is a common sequela of these treatments. The modified submandibular gland transfer (M‐SGT) procedure was developed to decrease xerostomia in the treatment of oral cavity cancer by sparing one submandibular gland (SMG) from radiation. This study's objectives were to: 1) elucidate the radiation‐sparing capacity of the M‐SGT, and 2) study the xerostomia‐reducing potential of the M‐SGT based on the University of Washington Quality‐of‐Life Questionnaire (UW‐QOL). Methods: Radiation therapy treatment plans were reviewed for all patients treated with surgery and RT who had a M‐SGT at the University of Alberta Hospital during the study period. Outcomes included: 1) radiation dose received by the transferred SMG within the periparotid area compared to the submandibular triangle (ST), and 2) patient‐reported saliva scores on the UW‐QOL compared to historical controls without a gland transfer. Results: Twenty‐two patients were included. The mean radiation dose received by the transferred SMG was 29.00 grays (Gy) (standard deviation 14.59 Gy), thus reducing the mean radiation dose to the SMG by a statistically significant 18.34 Gy (confidence interval 95% (13.37, 23.32), P < 0.01) compared to the ST and below the D50 of the SMG (34 Gy). Sixty‐five percent of patients rated their saliva as normal or mildly reduced on the UW‐QOL as compared to 16% of controls ( P = 0.01). Conclusion: The M‐SGT technique is successful at reducing the radiation dose sustained by the SMG during adjuvant treatment and provides a significant improvement in xerostomia‐related functional outcomes as compared to historical controls not receiving a gland transfer. Level of Evidence: 4 Laryngoscope, 130:925–929, 2020